Management Practices and Body Characteristics of Sudan Desert sheep (Hamari type) Raised on Range condition at West Kordofan State Sudan. - Bushara, Omer M.; Babiker, Salih A. (Journal of Veterinary Medicine and Animal Production, 2021)
The production potential of Hamari sheep, particularly flock size, structure, and management practices under range condition were investigated in Geibash locality, West Kordofan State, Sudan. The flock size was of three types, small (56), medium (156), and large (403). Breeding females constituted 50% of the flock, breeding male ranged from 3 to 5%, castrates represented 22 to 23% in small and medium flocks and 31% in large ones. Suckling lambs ranged from 5 to 7%, while weaned lambs constituted 3 to 8% in the different flocks. Management practices included, weaning, castration, and branding of young which were done at the third month of age. Castration practice was mainly to control breeding and fattening. The main methods used were crushing of spermatic cords between two wood rods (92.1%), and the Burdizzo 7.9%. Identification of animal was done mainly by fire brandingear cutting. Feeding depended mainly on natural pasture. Live weight of Hamari sheep ranged from 35.03 ± 0.97 to 60.94 ±2.01 kg, four milk teeth to three pairs of permanent incisors. The mean weight of mature males was greater than that of mature females. Body measurements showed progressive increase with age and sex appeared to have significant effect on these parameters. The study recommends increase of the percentage of breeding females in sheep flocks, giving supplementary feeding to all flocks during summer when pasture deteriorates and abandoning of breeding control. Establishment of more water points (rain water harvesting and drilling of wells) will reduce energy lost in search of water. These practices will lead to increase of lamb crop. More human method of castration should be encouraged as the use of Burdizzo, rubber rings or chemical castration.